The value of vocational education and training in advancing human development and reducing inequalities: the case of Palestine - Hilal, Randa (2018)
This thesis aims at examining the contribution of Vocational Education and Training (VET) to advancing Human Development (HD) and reducing inequality, using the example of Palestine as case-study rich in multi-layered inequalities, some of which are experienced in the region and worldwide, while others are specific to adverse conditions. The case of Palestine provides fertile ground for understanding inequality and human development, and for echoing the developed knowledge through to the understanding of VET and HD globally. The thesis contributes to the previous work on VET and HD introduced by McGrath (2012c) and shaped by many scholars, including McGrath and Powell, through the Capability Approach (CA). It uses Powell’s (2014) work on “aspiration” and capability lists (CL) and relates VET to human development within the Palestinian context. The thesis provides empirical evidence of the VET Learners’ and graduates’ capabilities and functions achievements through VET in the adverse conditions present in the Palestinian context. The thesis validates and develops the VET CL, integrating inequality elements and linking it to political economy theory. The thesis utilises Gender and Development Theory (GAD), complemented by the intersectionality approach. The research borrows Kabeer’s (1999) “empowerment framework”, based on the notion of “choice” in addressing disempowerment, to analyse how VET can contribute to reducing inequality. The thesis also engages with Political Economy arguments and specifically the work of Phillip Brown, Andy Green and Hugh Lauder (2001) on the need for “social transformation” to achieve the aim of a high skill society, suggesting an increased role for government and social partners and the political will for skills upgrading. In this regard, the thesis analyses how adopted policies are used to reduce or reproduce inequalities. The research used quantitative and qualitative methods, and engaged 1,240 people representing VET graduates, students, teachers, counsellors and management of VET institutes, in addition to policymakers on national and regional levels, as well as teachers and principals of general schools, employers, community representatives and government officials. 33 VET institutions were engaged representing the different VET providers being; governmental, non-governmental, semi-governmental and UN bodies. Selected institutes and consulted people presented different identified inequality elements. The Thesis presented empirical evidence on the increased value of VET for the marginalised, and for marginalised communities in adverse conditions. It presented that VET graduates’ achievements in employment, self-employment and different kind of work as well as in their speed in transiting to the World of Work (WOW) in comparison to their peers. Also presented their ability to generate income and other economic resources for poverty reduction and starting new families. In addition, it highlighted the empowerment achievements of the graduates and its link to achieving their aspirations. Confirming the transformation of the graduates through empowering the dis-empowered. Nevertheless, graduates were faced with internal and external structural challenges. Internal in social attitudes and institutional policies and measures, while the external is in the military occupation and its effects on mobility and socio-economic status. The structural challenges have clearly affected graduates functionings, and achievements of empowerment and aspirations. The thesis presented models of institutes and best-practices by others to support VET learners in overcoming some of the internal challenges, and highlighted the deficits in national policies and measures, it also highlighted a major international deficit. In addition, the thesis has presented the VET contribution to marginalised community resilience. The thesis presented methods of measuring empowerment, functionings and achievement of aspirations as voiced out from VET graduates and learners and triangulated with other resources. One of the main contributions of the thesis is in bringing in GAD to CA in HD approach to VET, and in linking them to political economy, providing a holistic framework to examine VET contribution to HD and reducing inequality. The thesis was able to link arguments about VET and inequality in an international context, and provided empirical evidence for the significance of the link between VET and empowerment in the reduction of inequality, thus indicating the importance of VET in the debate on inequality, and the importance of empowerment measures and goals for identifying the role of VET in reducing inequality and advancing human development.